On-Farm Welfare Assessment Protocol for Suckling Piglets: A Pilot Study - Marika Vitali; Elena Santacroce; Federico Correa; Chiara Salvarani; Francesca Paola Maramotti; Barbara Padalino; Paolo Trevisi (Animals, 2020)
Piglets experience welfare issues during the nursery phase. This pilot study aimed to test a protocol for identifying the main welfare issues in suckling piglets and to investigate relationships among animal-based indicators and management conditions. Litters (n = 134), composed of undocked and tail-docked piglets, were assessed at two farms. After birth, observations were made at the age of 7 days and 20 days. At each observation, housing conditions (HCs) were measured, and 13 animal-based indicators, modified from Welfare Quality, Classyfarm, Assurewel and others introduced ex novo, were recorded. A generalized linear mixed model was used, considering animal-based indicators as dependent variables and farm, piglets’ age, tail docking and HCs as independent variables. The main welfare issues were lesions of the limb (32.6%) and the front area of the body (22.8%), a poor body condition score (BCS) (16.1%), ear lesions (15.5%), and tail lesions (9.7%). Negative social behaviour (e.g., fighting and biting) represented 7.0% of the active behaviour, with tail biting observed in 8.7% of the piglets. While lesions on the front areas of the body were mostly associated with the farm, tail lesions, low BCS, tear staining, and diarrhoea were associated with light and nest temperature (p < 0.05). In particular, tail biting increased with scarce light (p = 0.007). Tail docking did not influence any animal-based indicator except for tear staining which was higher in the tail-docked as compared to the undocked piglets (p = 0.05), increasing awareness on this practice as a source of negative emotion in piglets. The protocol tested may be a promising tool for assessing on-farm piglets’ welfare.